REMEMBERING AND FORGETTING: THE HISTORY OF SHEIKH YUSUF STRUGGLE FOR HUMAN RIGHT - Erman, Erwiza (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2012)
For 300 years,. the name of Sheikh Yusuf, son of Macassar was missing from the government's attention and public intellectual as well. But when Nelson Mandela, President of South Africa,. commemorated 300 years of the arrival of Sheikh Yusuf in Cape Town in 1994, since that time government institution civil society and academics from Indonesia and South Africa have been paying to attention to remember, understand and study him from various perspectives. By using concept of remembering and forgetting, this article shows that the process of remembering by the two countries did not take place in the empty space, but rely on psychological consideration of the individuals, communities and socio-political condition from the two countries. The process of forgetting constructed by the Dutch colonial state in 17th century became inversely proportional to the action of remembering the Sheikh Yusuf by African and Indonesian officials in 20th century. The proces of remembering shows its own dynamics ranging from individuals communities to public memory. When remembering Syekh Yusuf reached state memory or public memory it became a power that can define and plan a socio-political and economic agenda for the future by the countries.